The interlocutive face of personal academic documents - Assumpção, Glória de Fátima Pinotti de [UNESP] (Universidade Estadual de Maringa, 2024)
This paper analyzes the interlocutive face of personal academic documents within the scope of Gaudin´s Socioterminology (1993), the Ducrot´s interlocution (1987), the Cabré´s Communicative Theory of Terminology (1999) and Maingueneau´s Discourse (2001). We form the hierarchical degrees in the Brazilian Educational System in relation to the temporal space in the scope of Guidelines and Bases of National Education LDB 5692/1971 and 9394/1996 and the complementary laws. The analysis of these terms in their usage context are based on the Terminological and Discursive Approach (ATD) through which terms are mandatory discourses, reproduced in environments of the work situations, with injunctive texts, whose textual genres in the researched domain, resemble the control of actions, measures, and modes of elaboration and execution and of interlocutors of a community of specialists in their workstations. Through this research, we recognize the main characteristics that underlie the formation of this terminology, the textual interlocution the morphosyntactic and lexical-semantic aspects. We concluded that the interlocution take place at different hierarchy institutional levels; through written texts, they are reproduced in different instances of legal documents and by different interlocutors. The terms are concretized by textual genres in a situated socio-historical context; in discourses as a social and political record, in which the speakers are present in the textual interlocution in a non-face-to-face way, that is, without there being face-to-face the term is the result of a construction between speaker and interlocutors. At least, also there is formation of a semantic network around a base term adding news denotations. This paper is part of the research entitled ‘The Terminology Profile of Personal Academic Documents’.
A face interlocutiva dos documentos escolares individuais
Keywords: specialized texts; Terminological-Discursive Approach (ATD); terminology; textual interlocution